Morphology and life history of an ant parasitoid, Psilocharis afra (Hymenoptera: Eucharitidae) - Heraty, John M.; Burks, Roger A.; Mbanyana, Nokuthula; Noort, Simon Van (Zootaxa, 2018)
Eucharitidae (Hymenoptera) are specialized ant (Formicidae) parasitoids. As we begin to develop a better understanding of their phylogenetic relationships, it is critical to establish baselines for morphological and biological data. A morphological review and the first report of life history data for Psilocharis afra Heraty is provided based on new material from the Mpumalanga Province of South Africa. Psilocharis Heraty is included in Eucharitinae, but it is unclear whether it is the sister group of all other members of the subfamily, or sister group to Neolosbanus Girault in a monophyletic Psilocharitini, which would in turn be sister group to Eucharitini. The oviposition habits of P. afra differ from those of other Eucharitidae in that eggs are placed among trichomes under bracts at flower bases, instead of either being inserted into cavities formed in plant tissue by an enlarged ovipositor (as in Oraseminae and some Neolosbanus) or inserted into cavities in plant tissue, as in most Eucharitini. The egg and first-instar planidia larva are described, and adult morphology is discussed with reference to Eucharitidae and other parasitoid Hymenoptera.